2016
DOI: 10.1016/j.jpain.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Inhibits the Development of Hyperalgesia and Sensitization of Spinal Nociresponsive Neurons in Type 2 Diabetes

Abstract: Thiazolidinedione drugs (TZDs) such as pioglitazone are FDA-approved for the treatment of insulin resistance in type 2 diabetes. However, whether TZDs reduce painful diabetic neuropathy (PDN) remains unknown. Therefore we tested the hypothesis that chronic administration of pioglitazone would reduce PDN in Zucker Diabetic Fatty (ZDFfa/fa) rats. Compared to Zucker Lean (ZLfa/+) controls, ZDF developed: (1) elevated blood glucose, HbA1c, methylglyoxal and insulin; (2) mechanical and thermal hyperalgesia at the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 109 publications
3
36
0
7
Order By: Relevance
“…Therefore, in addition to behavior, we test the hypothesis that intraplantar injection of MG evokes activation of spinal nociresponsive neurons by evaluating the phosphorylation of extracellular signal-regulated kinase (p-ERK) in the spinal cord dorsal horn. P-ERK is an established marker of pain-related central sensitization (Ji et al, 1999 , 2009 ; Gao and Ji, 2009 ) and is exacerbated in conditions of peripheral nerve injury (Morgenweck et al, 2013 ), inflammation (Corder et al, 2013 ), and type 2 diabetes (Griggs et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to behavior, we test the hypothesis that intraplantar injection of MG evokes activation of spinal nociresponsive neurons by evaluating the phosphorylation of extracellular signal-regulated kinase (p-ERK) in the spinal cord dorsal horn. P-ERK is an established marker of pain-related central sensitization (Ji et al, 1999 , 2009 ; Gao and Ji, 2009 ) and is exacerbated in conditions of peripheral nerve injury (Morgenweck et al, 2013 ), inflammation (Corder et al, 2013 ), and type 2 diabetes (Griggs et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because pain hypersensitivity can persist long after the healing of the initial damage, it causes major health problems around the world [2] . Interestingly, many patients with systemic disorders, such as spinal cord injury (SCI) [3] and diabetes [4] , suffer from hyperalgesia. Almost all of these patients accompany with oxidative stress when excessive amount of reactive oxygen species (ROS) are formed or when the antioxidant capacity is decreased [5] , [6] , and such imbalance may be a key factor to hyperalgesia [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with PPARγ ligands, such as pioglitazone, in the SNT model indicates that pioglitazone alleviates neuropathic pain through the attenuation of the up-regulation in proinflammatory cytokines [30]. The effect of pioglitazone in reducing pain may be mediated by a decrease in glial activation and through neuropathic non-genomic and genomic activity [31]. It has been shown that inflammatory cytokines and oxidative stress decrease the expression of PPARγ mRNA in adipocytes [32] and thiazolidinediones reverse this effect [33].…”
Section: Discussionmentioning
confidence: 99%